PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GIVING QUESTION ANN GETTING ANSWER (GQGA) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 32 PADANG TAHUN PELAJARAN 2013/2014 - Yeni, Silvi; Rahmi, Rahmi; Yunita, Alfi (Pendidikan Matematika, 2014)
AbstractÂ TheÂ  comprehension of the mathematical concept studentsâ are still low of class VIII SMPN 32 Padang becomes problem which is background this research. The purpose of this research is to know determine whether the ability of student understanding of mathematical concepts by implementing Giving Question and Getting Answer (GQGA) is better than the ability of student understanding of mathematical concepts with conventional learning class VIII SMPN 32 Padang. This research is experimental research with research design randomized on subject. The data analysis used was one way t test by using program MINITAB. Based on the calculation results obtained P-value = 0.000 is smaller than the significance level (Î±) = 0,05 so it can be concluded that the ability of student understanding of mathematical concepts using Giving Question and Getting Answer (GQGA) is better than the ability of student understanding of mathematical concepts with conventional learning class VIII SMPN 32 Padang.Â